2017
DOI: 10.1111/tpj.13632
|View full text |Cite
|
Sign up to set email alerts
|

Production of low‐Cs+ rice plants by inactivation of the K+ transporter OsHAK1 with the CRISPR‐Cas system

Abstract: The occurrence of radiocesium in food has raised sharp health concerns after nuclear accidents. Despite being present at low concentrations in contaminated soils (below μm), cesium (Cs ) can be taken up by crops and transported to their edible parts. This plant capacity to take up Cs from low concentrations has notably affected the production of rice (Oryza sativa L.) in Japan after the nuclear accident at Fukushima in 2011. Several strategies have been put into practice to reduce Cs content in this crop speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(43 citation statements)
references
References 64 publications
1
41
0
1
Order By: Relevance
“…Thus, RCs absorption and translocation appear to be controlled by different mechanisms in wheat, and RCs accumulation in the grain should be analyzed by carefully discriminating between absorption and translocation. The various mechanisms of RCs uptake in relation to K transporters have been reviewed 1,8 , and recently, several possible transporters involved in regulating RCs uptake have been reported 23,24,47 . Kojima et al also detected large variations among rice varieties in RCs translocation from shoot to grain 20 .…”
Section: Residual (Soilmentioning
confidence: 99%
“…Thus, RCs absorption and translocation appear to be controlled by different mechanisms in wheat, and RCs accumulation in the grain should be analyzed by carefully discriminating between absorption and translocation. The various mechanisms of RCs uptake in relation to K transporters have been reviewed 1,8 , and recently, several possible transporters involved in regulating RCs uptake have been reported 23,24,47 . Kojima et al also detected large variations among rice varieties in RCs translocation from shoot to grain 20 .…”
Section: Residual (Soilmentioning
confidence: 99%
“…Therefore, the movements of pollutants normalized by those of essential elements can provide important information for comparing or understanding the behavior of pollutants under specific conditions. Recent studies indicated both similarity and specificity in the behavior of potassium and cesium in plants [44,45]. The difference in their behavior suggests the unique nature of plant transporters towards elemental affinity, even if the elements have a high chemical similarity.…”
Section: Prospective Imaging Techniquesmentioning
confidence: 99%
“…also collaborate). Using the C.R.I.S.P.R./Cas9 system, they have developed a variety of rice that is capable of not selectively absorbing the caesium from the earth and that this radioactive substance does not contaminate the edible parts of the plant (Nieves-Cordones, 2017;Nieves-Cordones et al, 2017).…”
Section: Genetic Edition Through Crispr/cas9mentioning
confidence: 99%